Conformity of Textbooks with the Goals of Personality Education Set by Lithuanian Education being Reformed on the Base of Ideas of Humanistic Paradigm, as a Qualitative Prerequisite - Bruzgelevičienė, Ramutė (Pedagogika, 2015)
During the first decade of Lithuanian educational reform based on the shift in education paradigms textbooks were considered the main source of teaching and were supposed to help to seek new goals in personality education as well as strengthen the paradigm being implemented. Traditionally, textbook was seen as the only teacher tool in that period. However, according to the research carried out in the first decade of the 21st century, textbook along with accompanying printed material still remains the most often used tool in a Lithuanian classroom that pupils continue to use as their main means of study. It is essential that the state level educational documents regulating quality of textbooks include such qualitative criteria that would direct textbooks toward complying with the principles of humanistic paradigm and implementing the goals of personality education. The object of research is the extent to which regulations of the documents monitoring quality of textbooks are focused on implementation of the personality education goals set by Lithuanian education being reformed on the base of humanistic paradigm of education. As a method, qualitative research using documentary research strategy has been chosen for this article, primary documentary sources are examined and the results are analyzed according to the stages of Grounded Theory, i.e. coding, theoretical sampling and comparing. Having conducted comparative analysis of the documents regulating quality of textbooks with specific character education goals as well as content of categories and subcategories expressing humanistic paradigm of education, the following conclusions are drawn: At the outset of Lithuanian Educational Reform, when discussing demands for suitable teaching tools in the schools being reformed, the scientists projected the shift from objectivist approach common to authoritarian soviet school to a constructivist one, underlined necessity to cooperate with a person’s nature, i.e. they directed focus to humanistic paradigm of education and brought the goals of textbooks to seek personality education up-to-date. In the analyzed group of documents regulating quality of textbooks no sustainable system of quality criteria has settled, but the task set for textbooks to seek character education goals, as a quality field, has remained stable throughout the whole period of educational reform. The documents regulating quality of textbooks do not designate their paradigmatic orientation, therefore there is a clear paradigmatic confusion when discussing a concept of a textbook (its purpose, function, methodological setup etc.) both when it comes to comparing documents from different years and certain documents within themselves. This paradigmatic confusion in the document statements remains stable throughout the whole period of educational reform.